Protective effect of cinnamicaldehyde in endotoxin poisoning mice. (1st November 2016) - Xu, Feng; Wen, Taoqun; Wang, Feng; Sang, Wentao; Zeng, Nan
Abstract: Context: Several pharmacological studies have shown that cinnamicaldehyde (CA) has anti-inflammatory and anti-tumor effects, but no data show the effects of CA on the endotoxin poisoning. Objective: In this work, the protective effect of CA in LPS-induced endotoxin poisoning mice was investigated. Materials and methods: Mice were randomly divided into normal, LPS, LPS +5 mg/kg dexamethasone (DEX), LPS +0.132 g/kg CA, and LPS +0.264 g/kg CA group. Pretreated with CA (0.132 and 0.264 g/kg/day, respectively) for 5 consecutive days before LPS injection. Except the normal group, the other animals were intraperitoneally injected with LPS (15 mg/kg). Results: Twelve hours after LPS injection, CA significantly reduced the production of pro-inflammatory cytokines (interleukin-18, interleukin-1β, and interleukin-5) and chemokines (macrophage colony stimulating factor, macrophage inflammatory protein-1β) in serum. In addition, the histopathological study indicated that CA attenuates lung injury induced by LPS. Moreover, the numbers of neutrophils were significant decreased and the NF-κB (p65) mRNA level was reduced in lung after treated with CA. Conclusion: The present data suggest that cinnamicaldehyde can be considered as potential therapeutic candidates for the endotoxin-poisoning-related diseases such as sepsis via its anti-inflammation effects.